School climate and academic performance of secondary school students in an educational institution in Huánuco. - Grandes Anapan, Manuel Eliab (2025)
Objective. To determine the relationship between school climate and academic performance in students of Parish Educational Institution San Luis Gonzaga in Huanuco. Methods. Study type was observational and cross-sectional, with a quantitative approach. Population comprised of 182 students, and 126 students were selected by a probabilistic sampling by strata. Instruments used were scale of school social climate and grades report of academic performance. Descriptive and inferential analysis was performed using Pearson’s correlation coefcient. Results. Regarding school climate, it was observed that 63% obtained a “good” result, 19% “regular”, 14% “poor”, 2% “very good”, and 2% “excellent”. On the other hand, regarding school performance achievement, an “expected” achievement (17-14) of 73%, “in process” (13-11) of 16 % and “outstanding” (20-18) of 10%. Therefore, “good” school climate and “expected” school achievement performance (16-14) stand out with a higher  percentage. Conclusion. The correlation between school climate and academic performance was positive at a moderate level. In conclusion, research hypothesis was accepted.